Expression, signal transduction, and function analysis of TIRAP and TRIF in Nile tilapia (Oreochromis niloticus). (April 2021) - Trung, Nguyen Bao; Nan, Fan-Hua; Wang, I-Jong; Wu, Yu-Ching; Wen, Chiu-Ming; Lee, Meng-Chou; Hang, Ho Thi; Lee, Po-Tsang
Abstract: Toll/interleukin 1 receptor domain-containing adaptor protein (TIRAP) and toll/interleukin 1 receptor-domain-containing adapter-inducing interferon-β (TRIF) are crucial adaptors of signal transduction for the signaling pathways of toll-like receptors (TLRs). TIRAP and TRIF perform an essential function in an antimicrobial immune response; however, their function in Nile tilapia remains unknown. Herein, TIRAP and TRIF from Nile tilapia were identified and functionally characterized. Phylogenetic analysis showed that OnTIRAP and OnTRIF clustered with corresponding homologs from other fish species, with comparable gene structures to those of select vertebrate TIRAP and TRIF genes, respectively. The expression profiles of OnTIRAP and OnTRIF were broadly distributed in the ten tissues investigated, with high transcript levels noticed in immune organs. The transcription levels of OnTIRAP and OnTRIF were upregulated in response to bacterial and poly (I:C) challenges. GFP signals were only detected in the cytoplasmic region of fish cells transfected with OnTIRAP-GFP and OnTRIF-GFP expression plasmids. Moreover, overexpression of OnTIRAP and OnTRIF activated interferon-β (IFN-β) and activator protein 1 (AP1) reporters in HEK 293 cells. Activation of the nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) reporter was only observed in OnTRIF-overexpressing HEK 293 cells. Furthermore, the results of the co-immunoprecipitation analysis showed that OnTRIF, but not OnTIRAP, was recruited as an adaptor protein by OnTLR25. This study provides the first evidence on the functions of OnTIRAP and OnTRIF in the immune system of Nile tilapia against pathogens and may serve as the basis for further investigations on TLR signaling in fish. Highlights: Nile tilapia TIRAP and TRIF orthologs were cloned. OnTIRAP and OnTRIF increase significantly after bacterial and poly (I:C) injection. OnTIRAP activates IFN-β, AP1, and fails to induce the NF-κB reporter in HEK 293 cells. OnTRIF can activate the NF-κB, IFN-β, and AP1 reporters in HEK 293 cells. OnTLR25 recruits OnTRIF as its adaptor protein.